Diagram of concrete dynamic deformation confined by CFRP jackets. Issue 5 (June 2020) - Ubysz, Andrej; Zhiharev, Fedor; Chernik, Vladimir; Dekhterev, Denis
Abstract: A review of the current state of the issue of describing the deformation of columns confined by CFRP jackets under of dynamic loading is carried out. The insufficiency of the study of elements under the influence of axial dynamic load is indicated. The dynamic increase factors (DIF) for concrete and CFRP, which are obtained by the results of existing experiments, are substantiated. Using the principle of the invariance of the potential energy of deformation of concrete at the time of its destruction under regime loading, a formula is obtained for determining DIF for ultimate relative strain of unconfined concrete. Based on the assumption of the same law of concrete deformation under static and dynamic loading, was obtained a diagram of concrete dynamic deformation confined by CFRP jackets. The diagram is valid in the range of strain rates 10 −3 -10 2 s −1 . A comparison is made between a static diagram and a dynamic diagram derived from it. The characteristic of the main sections of the diagram is given. An increase in the strength and ductility of confined concrete at the initial stage of loading is obtained. At stresses equal to the tensile strength of limited concrete, its ductility is somewhat reduced. It was revealed that a significant increase in the bearing capacity of confined concrete begins at strain rates of 10 s −1 or more.